Distally-referred surface electrical nerve stimulation (DR-SENS) for haptic feedback - Mesias, Luis; Gormez, M Akif; Tyler, Dustin J; Makowski, Nathaniel S; Graczyk, Emily L; Fu, Michael J (Journal of neural engineering, 2023)
This study's objective is to understand distally-referred surface electrical nerve stimulation (DR-SENS) and evaluates the effects of electrode placement, polarity, and stimulation intensity on the location of elicited sensations in non-disabled individuals. A two-phased human experiment was used to characterize DR-SENS. In Experiment One, we explored 182 electrode combinations to identify a subset of electrode position combinations that would be most likely to elicit distally-referred sensations isolated to the index finger without discomfort. In Experiment Two, we further examined this subset of electrode combinations to determine the effect of stimulation intensity and electrode position on perceived sensation location. Stimulation thresholds were evaluated using parameter estimation by sequential testing and sensation locations were characterized using psychometric intensity tests. We found that electrode positions distal to the wrist can consistently evoke distally referred sensations with no significant polarity dependency. The finger-palm combination had the most occurrences of distal sensations, and the different variations of this combination did not have a significant effect on sensation location. Increasing stimulation intensity significantly expanded the area of the sensation, moved the most distal sensation distally, and moved the vertical centroid proximally. Also, a large anodic-leading electrode at the elbow mitigated all sensation at the anodic-leading electrode site while using symmetric stimulation waveforms. Furthermore, this study showed that the most intense sensation for a given percept can be distally referred. Lastly, for each participant, at least one of the finger-palm combinations evaluated in this study worked at both perception threshold and maximum comfortable stimulation intensities. These findings show that a non-invasive surface electrical stimulation charge modulated haptic interface can be used to elicit distally-referred sensations on non-disabled users. Furthermore, these results inform the design of novel haptic interfaces and other applications of surface electrical stimulation based haptic feedback on electrodes positioned distally from the wrist.